Two decades of experience of the Fabry Outcome Survey provides further confirmation of the long-term effectiveness of agalsidase alfa enzyme replacement therapy - Uma Ramaswami; Guillem Pintos-Morell; Christoph Kampmann; Kathleen Nicholls; Dau-Ming Niu; Ricardo Reisin; Michael L. West; Christina Anagnostopoulou; Jaco Botha; Dalia Jazukeviciene; Jörn Schenk; Derralynn A. Hughes; et al. (Molecular Genetics and Metabolism Reports)
Background: Analyses of up to 20 years of data from the Fabry Outcome Survey (FOS) assessed the long-term effectiveness of agalsidase alfa enzyme replacement therapy. Methods: The impact of agalsidase alfa treatment on renal, cardiac, morbidity, and mortality outcomes in FOS was compared with untreated external Fabry disease (FD) cohorts. Results: A total of 2171 FOS patients (1014 men, 919 women, 163 boys, 75 girls) received agalsidase alfa (median [range] duration of treatment: 5.38 [0.0–20.8] years). Annual rates of decline in estimated glomerular filtration rate improved in treated patients versus untreated external cohorts regardless of sex or baseline urinary protein levels. Annual left ventricular mass index rates were stable in treated patients regardless of sex or baseline left ventricular hypertrophy status, and better than in untreated external cohorts. The mean age at which 50 % of patients had their first composite morbidity event was later in the agalsidase-alfa-treated population than in the untreated external cohort (51.7 vs 41 years [males]; 60.8 vs 53 years [females]). After 24 months of treatment, the probability of a composite morbidity event was ∼34 % in treated patients and ∼ 45 % in untreated patients. Treated patients were older at death than untreated patients (mean [range]: 61.7 [26.2–87.6] vs 50.3 [34.5–70.1] years). The mean age at which 50 % of male patients were still alive was higher in treated patients than in untreated external cohorts (75.5 vs 60.0 years). Conclusions: Long-term treatment with agalsidase alfa may provide renal, cardiac, and overall survival protection in FD.